Penerapan Pendekatan Whole Language Untuk Meningkatkan Kemampuan Membaca Siswa Kelas IV SD Negeri 40 Lumpangan Kecamatan Paj’ukukang Kabupaten Bantaeng - Pratiwi, Salsabila; Azis, Sitti Aida; Rajab, Abd (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
Identification of the problem is that students are less focused on learning to understand the content of the reading. This research aims to describe the application of the Whole Language approach in improving students' reading skills in class IV Indonesian language lessons at SD Negeri 40 Lumpangan, Paj'ukukang District, Bantaeng Regency. This type of research is class action research (Class Action Research) which consists of two cycles where each cycle is carried out in four meetings. The focus of this research is 1) Reading comprehension skills and 2) Use of the Whole Language approach in class IV of SD Negeri 40 Lumpangan, Paj'ukukang District, Bantaeng Regency. Research procedures include planning, implementing actions, observing and reflecting. The research subjects were 20 class IV students. The collected data was analyzed using quantitative and qualitative analysis. The results of this research are that there is an increase in student learning activities from cycle I to cycle II, student learning outcomes have increased, namely the average score of student learning outcomes in cycle I is 63, increasing in cycle II to 83. Students' reading comprehension and learning completion has also increased, where in cycle I, 8 (40%) students achieved learning completeness, while in cycle II 20 (100%) students achieved learning completeness and classical learning completion was achieved. This means that learning completeness in cycle II was achieved classically because the number of students who completed it was more than 80%. Based on the results of the research above, it can be concluded that the reading comprehension skills of class IV of SD Negeri 40 Lumpangan, Paj'ukukang District, Bantaeng Regency through the application of the Whole Language approach have increased.